4(-4x+4)=-2(6x-8)

Simple and best practice solution for 4(-4x+4)=-2(6x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(-4x+4)=-2(6x-8) equation:



4(-4x+4)=-2(6x-8)
We move all terms to the left:
4(-4x+4)-(-2(6x-8))=0
We multiply parentheses
-16x-(-2(6x-8))+16=0
We calculate terms in parentheses: -(-2(6x-8)), so:
-2(6x-8)
We multiply parentheses
-12x+16
Back to the equation:
-(-12x+16)
We get rid of parentheses
-16x+12x-16+16=0
We add all the numbers together, and all the variables
-4x=0
x=0/-4
x=0

See similar equations:

| 2x+4x-1=x+4 | | -7s+20=-9s-20 | | 16/5x=5/2 | | 10x+2-(2x)=18 | | 12=-5p+p | | 5n+2n+4=18 | | -36x=14,580 | | 17x+85=-170 | | -5+7(2x-2)=-16-31 | | −3v−12=2v−37 | | 990/p=32 | | (-7.4)+t=9.11 | | (11y-1)=157 | | 2x+184=-6 | | -3v-12=2v-37−3v−12=2v−37 | | -2a+15+5a=6a-8a | | 5x²+405=0 | | -8v+6(v+4)=32 | | 3(g+2)=3g+6 | | -6+15x=-9 | | -6u+4(u+2)=10 | | .16=n-21 | | (8x+4)=(10x-6) | | 10x-(3x)=42 | | 8x+88=-8 | | -8(3k-6)=-144 | | 3(x-4=x+2x-12 | | .16=n+21 | | 4(x–2)+4x–1=x+2(x–3) | | 6n-6n-12=14-12 | | -24x+14=518 | | 3=x-(10/x) |

Equations solver categories